Improved piggyBac Transformation with Capped Transposase mRNA in Pest Insects - Häcker, Irina; Rehling, Tanja; Schlosser, Henrik; Mayorga-Ch, Daniela; Heilig, Mara; Yan, Ying; Armbruster, Peter A.; Schetelig, Marc F.; Justus Liebig University Giessen (My University, 2023)
Creating transgenic insects is a key technology in insect genetics and molecular biology. A widely used instrument in insect transgenesis is the piggyBac transposase, resulting in essentially random genomic integrations. In contrast, site-specific recombinases allow the targeted integration of the transgene construct into a specific genomic target site. Both strategies, however, often face limitations due to low transgenesis efficiencies. We aimed to enhance transgenesis efficiencies by utilizing capped mRNA as a source of transposase or recombinase instead of a helper plasmid. A systematic comparison of transgenesis efficiencies in Aedes mosquitoes, as models for hard-to-transform insects, showed that suppling piggyBac transposase as mRNA increased the average transformation efficiency in Aedes aegypti from less than 5% with the plasmid source to about 50% with mRNA. Similar high activity was observed in Ae. albopictus with pBac mRNA. No efficiency differences between plasmid and mRNA were observed in recombination experiments. Furthermore, a hyperactive version of piggyBac transposase delivered as a plasmid did not improve the transformation efficiency in Ae. aegypti or the agricultural pest Drosophila suzukii. We believe that the use of mRNA has strong potential for enhancing piggyBac transformation efficiencies in other mosquitoes and important agricultural pests, such as tephritids.
Keywords: ddc:630